Diagnostic Efficacy of Dynamic Radiothallium Uptake in Thyroid Nodules Determined by Computer-Assisted Scintigraphy - Palermo, F. (Nuklearmedizin - NuclearMedicine, 1989)
Radiothallium (201TI) has been proposed as a tracer in nuclear medicine for the diagnosis of cold thyroid nodules. Its potassium-mimetic characteristics, like those of 131Cs, can provide information on its turnover in the thyroid nodules; this serves as a basis for the distinction between benign and malignant thyroid tumours. The author presents a study on the diagnostic efficacy of 201TI as a tracer for thyroid nodules with the aim of evaluating the dynamic uptake and the biodistribution of 201TI after intravenous injection of 555–740 kBq/kg. A quantitative analysis was made by continuous scanning of 201TI distribution during the first 20–30 min following thallium injection, with further surveys from 40 to 60 min or more when fixation in a nodule was demonstrated. The ratio between 201TI uptakes in the nodule and in healthy tissue (density index) was calculated and a multiparametric analysis of the corresponding activity/ time curves was performed. This study included 176 patients. Concordance between clinico-histological diagnosis and radio-isotopic findings was demonstrated in 102 out of 106 colloidocystic goitres, in 42 out of 48 benign nodules including thyroiditis, and in 21 out of 22 malignant tumours; a significant statistical difference in the density index between solid and cystic nodules, but no difference between benign and malignant nodules; and a different201 Tl dynamic behaviour in nodules of different nature, with a clear statistical difference in the thallium release between malignant nodular and healthy tissue (nodular disappearance index). This method can improve the diagnosis value of scintigraphy for thyroid nodules enhancing the sensitivty of the radioisotopic applications in comparison with other non-invasive techniques.Radiothallium (201T1) wurde als nuklearmedizinischer Tracer für die Beurteilung von kalten Schilddrüsenknoten vorgeschlagen. Die Kalium- bzw. 131Cs-ähnliche Charakteristik ermöglicht die Erfassung des Umsatzes in Schilddrüsenknoten; hiermit kann eine Unterscheidung zwischen gutartigen und bösartigen Schilddrüsentumoren versucht werden. Vörgestellt wird eine Untersuchung zur Bestimmung der diagnostischen Aussagekraft von 201T1 als Tracer für Schilddrüsenknoten. Nach intravenöser Injektion von 555–740 kBq/kg wurden dynamische Speicherung und regionale Verteilung von 201T1 bestimmt. Durch die Funktionsszintigraphie wurde die regionale Verteilung von 201T1 während der ersten 20-30 min nach der Injektion quantitativ festgelegt; 40–60 min oder später wurde die Fixation im Schilddrüsenknoten erfaßt. Das Verhältnis der 201T1-Speicherung im Knoten zum normalen Gewebe (cts/Pixel) wurde errechnet und die entsprechenden Zeit-Aktivitätskurven einer Multiparameteranalyse unterzogen. Die Untersuchung beinhaltet 176 Patienten. Dabei fanden sich Übereinstimmung zwischen der klinisch-histologischen Diagnose und dem nuklearmedizinischen Befund in 102 von 106 Fällen mit kolloidzystischen Strumen, in 42 von 48 gutartigen Knoten inkl. Thyreoiditis und in 21 von 22 malignen Knoten. Eine signifikante Differenz in den Speicherwerten fand sich bei soliden im Vergleich zu zystischen, jedoch nicht zwischen gutartigen und bösartigen Knoten. Unterschiedliche Knoten zeigten unterschiedliches Verhalten von 201T1, wobei sich der 201T1- Verlust über die Zeit aus knotigem und gesundem Gewebe signifikant unterschied (Knoten-Verlust-Index). | Die vorgestellte Methodik kann den diagnostischen Wert der Schilddrüsen- knoten-Szintigraphie verbessern, wobei die Sensitivität nuklearmedizinischer Verfahren im Vergleich zu anderen nichtinvasiven Methoden erhöht wird.